A novel and facile synthesis of 3-(2-benzofuroyl)- and 3,6-bis(2-benzofuroyl)carbazole derivatives - Gao, Wentao; Zheng, Meiru; Li, Yang (Beilstein Journal of Organic Chemistry, 2011)
A facile synthesis of hitherto unreported 3-(2-benzofuroyl)carbazoles 3a–k, 3,6-bis(2-benzofuroyl)carbazoles 5a–k, and naphtho[2,1-b]furoylcarbazoles 3l and 5l is described. The synthesis mainly relies on the ultrasound-assisted Rap–Stoermer reaction of 3-chloroacetyl- (1) or 3,6-dichloroacetyl-9-ethyl-9H-carbazole (4) with various salicylaldehydes 2a–k as well as 2-hydroxy-1-naphthaldehyde (2l) in CH3CN with the presence of PEG-400 as catalyst. The procedure offers easy access to benzofuroylcarbazoles in short reaction times and the products are obtained in moderate to good yields.
Keywords: 2-benzofuroyl; carbazole; PEG-400; Rap–Stoermer reaction; salicylaldehydes; ultrasound-assisted